DIVERSIDADE DE HIMENÃ“PTEROS PARASITÃ“IDES (HYMENOPTERA) NA ESTAÃ‡ÃƒO ECOLÃ“GICA DE JATAÃ, LUIZ ANTÃ”NIO, SP, BRASIL - Perioto, Nelson Wanderley; Lara, RogÃ©ria InÃªs Rosa; Vacari, Alessandra Marieli; Favoreto, Luciany; Miranda, Natalia Furlan; Chagas Filho, Norton Rodrigues; Pessoa, Roseli (REVISTA DE AGRICULTURA, 2015)
DIVERSIDADE DE HIMENÃ“PTEROS PARASITÃ“IDES (HYMENOPTERA) NA ESTAÃ‡ÃƒO ECOLÃ“GICA DE JATAÃ, LUIZ ANTÃ”NIO, SP, BRASIL